2021
DOI: 10.21608/jcbr.2021.84374.1219
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of rosemary and costus on blood-associated toxicity in Ehrlich-bearing mice treated with cisplatin

Abstract: Background: Rosemary (ROLE) and costus (SLRE) have been established to show antioxidant effects. Aim: This study aimed to evaluate the ameliorating effects of ROLE and SLRE to the side-effects induced by cisplatin (CIS) in tumor-bearing mice. Materials and Methods: Extracts of ROLE and SLRE were examined for their phytochemical activities. To ecaluate their anti-tumor effects, mice were inoculated intraperitoneally (i.p.) with 2.5x10 5 Ehrlich ascites carcinoma (EAC) and then treated i.p. with CIS (dose????) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Within the scope of this study, flow cytometric analysis showed that HDN combined treatment with Cis induced an antitumor immune response by increasing the percentage of splenic T helper (CD3 + CD4 + ) and T cytotoxic (CD3 + CD8 + ) cells, while concurrently orchestrating a modulatory effect on CD4 + CD25 + regulatory cells accompanied by improving spleen proliferation, which regulate the immune response against tumor. Similarly, earlier investigations revealed the synergistic role of combined treatments with Cis on antitumor immunity (Ye et al, 2018;El-Bolkiny et al, 2021;Wang et al, 2022). Hassouna et al (2015) and Berköz et al (2021) documented that HDN can improve the immunosuppressive impact of diazinon and cyclophosphamide, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Within the scope of this study, flow cytometric analysis showed that HDN combined treatment with Cis induced an antitumor immune response by increasing the percentage of splenic T helper (CD3 + CD4 + ) and T cytotoxic (CD3 + CD8 + ) cells, while concurrently orchestrating a modulatory effect on CD4 + CD25 + regulatory cells accompanied by improving spleen proliferation, which regulate the immune response against tumor. Similarly, earlier investigations revealed the synergistic role of combined treatments with Cis on antitumor immunity (Ye et al, 2018;El-Bolkiny et al, 2021;Wang et al, 2022). Hassouna et al (2015) and Berköz et al (2021) documented that HDN can improve the immunosuppressive impact of diazinon and cyclophosphamide, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Within the scope of this study, flow cytometric analysis showed that HDN combined treatment with Cis induced an antitumor immune response by increasing the percentage of splenic T helper (CD3 + CD4 + ) and T cytotoxic (CD3 + CD8 + ) cells, while concurrently orchestrating a modulatory effect on CD4 + CD25 + regulatory cells accompanied by improving spleen proliferation, which regulate the immune response against tumor. Similarly, earlier investigations revealed the synergistic role of combined treatments with Cis on antitumor immunity (Ye et al, 2018;El-Bolkiny et al, 2021;. Hassouna et al (2015) and Berköz et al (2021) documented that HDN can improve the immunosuppressive impact of diazinon and cyclophosphamide, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…On the contrary, combined treatment with (HDN and Cis) improved these hematological alterations, hepatorenal toxicity, and oxidative stress toward normal values. Previous studies have reported toxic effects of Cis on bone marrow cell colonies that substantially affect blood cells and induce hematotoxicity (Das et al, 2003;Aldossary 2019;Ibrahim et al, 2020;El-Bolkiny et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Not only cancer is a public health disease, but also may have profound implications for immune defense [28] . However, chemotherapy used for cancer treatment has associated with varying profound side effects [2] . OXA, cisplatin, and carboplatin are the major platinum compound used in cancer chemotherapy [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the most common chronic disease; the information about the occurrence and the possibility of cancer therapy during pregnancy is increasing nowadays [1] . A variety of theses chemotherapeutic drugs was in a concomitant with significant toxic manifestations [2] . The kidney is crucial organ for the major function of the body.…”
Section: Introductionmentioning
confidence: 99%